Surgical techniques for restoration of elbow flexion in traumatic brachial plexus injuries: a single-center experience in Egypt - Mohamed E. Elsebaey; Mohamed E. Y. Elghabaty; Tamer M. Nasef; Hamdi Nabawi Mostafa; Mohamed F. Elfarsy (Egyptian Journal of Neurosurgery)
Abstract Background Traumatic brachial plexus injuries (BPIs) have multiple sub-types and clinical pictures. One of the severe clinical patterns that also has social and economic burden forms is the loss of the elbow flexion, so here in this study we show and discuss this clinical study that explain the surgical procedures that done by our team for restoration of the elbow flexion as it is a cardinal function of the upper limb. Purpose To evaluate the clinical outcome of various surgical procedures for restoring the elbow flexion in traumatic peripheral nerve injured patients at the department of neurosurgery at Benha teaching hospital, Benha city, Arab republic of Egypt. Study design A retrospective descriptive clinical study. Patients and methods Fifty-seven patients who had traumatic brachial plexus injury were operated by our team from January 2021 to January 2024. Data regarding the age, sex, causes of injury, patterns of injury, surgical approaches, surgical procedures and recovery outcome were collected. Results The team operated 57 patients for regaining the movement of the elbow flexion after brachial plexus injuries. All the patients were males with mean age 31 years, 72% encountered road traffic accidents, and 90% were because of motorbike accidents. 60% showed upper BPI. Neurolysis, direct repair and nerve transfer were the surgical procedures that were followed. Functional recovery had been achieved in about 61% of the study population. Conclusion We conclude that the nerve transfer is very efficient procedure for restoration of the elbow flexion including technique on innervation of the musculocutaneous nerve using the intercostal nerves or using the Oberlin technique, among traumatic brachial plexus injuries. But also, each patient has its own characteristics that must be taken in mind for ultimate choosing the type of the neve transfer and rehabilitation program after the surgery.